Short-time intensive insulin therapy upregulates 3 beta- and 17 beta-hydroxysteroid dehydrogenase levels in men with newly diagnosed T2DM - Hu, Yun; Wang, Ying; Cai, Ting-ting; Liu, Lu; Li, Dong-mei; Ma, Jian-hua; Ding, Bo (Frontiers in Endocrinology, 2022)
Objective Our previous study has found that short-term intensive insulin therapy in patients with newly diagnosed type 2 diabetes mellitus (T2DM) increased serum testosterone levels, but the underlying mechanisms remain unclear. Design and methods In this self-controlled study, 43 men with newly diagnosed drug naïve T2DM, aged 18-60 years, with HbA1c >9.0% were treated with continuous subcutaneous insulin infusion (CSII) to normalize blood glucose within one week. Venous blood specimens were collected for measuring of serum total testosterone, dehydroepiandrosterone sulfate (DHEA-S), 3β- and 17β-hydroxysteroid dehydrogenase (3β- and 17β-HSD) concentrations before and after insulin therapy. Results Testosterone increased from 13.0 (11.3, 14.6) nmol/L to 15.7 (13.9, 17.5) nmol/L after intensive insulin therapy (p<0.001), while the levels of DHEA-S decreased significantly after treatment (from 6.5 (5.7, 7.3) μmol/L to 6.0 (5.3, 6.7) μmol/L, p=0.001). The ratio of testosterone/DHEA-S increased significantly (2.4 (2.0, 2.8) vs. 3.1 (2.6, 3.7) nmol/μmol, p<0.001). After blood glucose normalization with the short-term CSII therapy, 3β-HSD increased from 11.0 (9.5, 12.5) pg/mL to 14.6 (13.5, 15.7) pg/mL, p=0.001, and 17β-HSD increased from 20.7 (16.3, 25.2) pg/mL to 28.2 (23.8, 32.5) pg/mL, p=0.009. Conclusions Blood glucose normalization via short-term intensive insulin therapy increases plasma total testosterone levels in men with newly diagnosed type 2 diabetes, associated with a decreased level of DHEA-S, probably because of the enhanced conversion from DHEA to testosterone catalyzed by 3β-HSD and 17β-HSD.